FOSTERING OPEN INNOVATION IN THE PUBLIC SECTOR THROUGH INCUBATORS AND ACCELERATORS - Веселинова, Надежда (E-Journal VFU, 2025)
The aim of this study is to explore the concept of open innovation in the public sector, with an emphasis on the role of incubators and accelerators as catalysts for innovation in public services. Attention is also directed to approaches for creating networks through incubators. In an effort to identify the main challenges and opportunities, the paper highlights the importance of strategic management of innovation processes and sheds light on a number of barriers that these innovation platforms may encounter. The objectives of the study are achieved through the methods of conceptual analysis, analytical approach, induction, synthesis, and others.
Keywords: innovation; open innovation; incubators; accelerators; public sector